The Context Within: The Play within the Play between Theatre Anthropology, System Theory and Postcolonial Critique - Čale Feldman, Lada (Array, 2007)
The discussion suggests that particular corpuses of playwrighting that are called for to typify the play within the play procedure may introduce specificities that challenge extant modes of formulating its supposedly universally valid mechanism and its various possible functions. The post-WWII Croatian play within the play strategies rely heavily on cultural and historical specificities of the theatrical production and reception, emphasizing the "context within".